Pengaruh Gaya Kepemimpinan, Kompensasi, dan Kepuasan Kerja terhadap Kinerja Karyawan PT. Kereta Api Logistik di Surakarta - Nahara, Alden Dhafi; Murwanti, Sri (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This research aims to analyze the influence of leadership style, compensation, and job satisfaction on employee peformance. The population and the sample of this research are employees who work in PT Kereta Api Logistik Surakarta with a total of 57 employees as respondent. The type of data that used in this research is primary data. The data collection method is to distribute questionnaires in the form of print out questionnaires, then it will be processed by using SPSS Statistic 26 software. The result shows that leadership style has a positive and significant effect on employee peformance. Compensation has a positive and significant effect on employee peformance. Job satisfactory has a positive and significant effect on employee peformance.